Pioneering Pathways: Universities and Industry as Collaborative Learners on the Road to Net Zero - Hornegger, Joachim; Zipse, Oliver (Springer International Publishing, 2023)
Successful sustainability transformation is a collective endeavour that demands innovative, science-based collaboration between academia and industry. Striving towards Net Zero, the mutual learning and integration of their strengths are imperative. This chapter features the introductory discussion between Joachim Hornegger, President of FAU Erlangen-Nürnberg, and Oliver Zipse, Chairman of the Board of Management of BMW AG, exploring the why and how of collaborative efforts in Sect. 1.3. This chapter also serves as an introduction to the book, offering in Sect. 1.4 an overview of key topics on ‘The Road to Net Zero’. These range from science-based targets to integrated strategies, reporting, and the pivotal role of technological innovations. While not presenting a blueprint solution, the described transformation journey-‘Road to Net Zero’ in this book-outlines a roadmap and encourages robust university-industry collaboration.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Learning; Road to Net Zero; Science-based management; Sustainability transformation; University-industry collaboration